The beast from the East - Stine, R. L. (New York : Scholastic, 1996)
Ginger and her identical twins, Nat and Pat, get lost in the woods and find themselves in very unfamiliar grounds as the grass it yellow, the bushes are purple, and the trees are very tall.
3.8
5-8
Keywords: Forests and forestry -- Juvenile fiction; Games -- Juvenile fiction; Forests and forestry -- Fiction; Games -- Fiction; Horror stories; Forests and forestry -- Fiction; Games -- Fiction; Horror fiction; Horror fiction